Characterization of microbial community assembly on new wooden vats for use in cheese production. (February 2023) - Sun, Lang; D'Amico, Dennis J.
Abstract: Wooden vats are used in the production of some traditional cheeses as the biofilms on wooden vat surfaces are known to transfer large quantities of microbes to cheese. However, very few studies have investigated the microbial composition of biofilms on newly developed wooden vats and how communities assemble and evolve. In the present study, the microbial communities of biofilms were characterized over the activation process on new wooden vats using amplicon sequencing of bacterial 16s rRNA and fungal internal transcribed spacer genes. Results showed that microbes from the whey effectively developed on wooden vats. Lactococcus was highly dominant throughout the vat activation process with substantial increases in the relative abundance of Acetobacter and Lactobacillus at the end of the vat activation (day 7). This was in contrast with fungal communities that stabilized early (day 1) and were dominated by Kluyveromyces . Predicted functions corresponded with the different stages of biofilm formation whereby functions associated with biofilm initiation were enriched on day 1 and those associated with growth and maturation were enriched on days 4 and 7. Microbial succession on wooden vat surfaces is expected to be reproducible based on the early onset and dominance of the deterministic process. Highlights: Microbes from cheese whey formed biofilms on new wooden vats within 7 days. Bacterial succession was observed throughout the vat activation process. Fungal community structure was established early in the process. Predicted functions corresponded with the different stages of biofilm formation. Microbial assembly on wooden vats was driven by deterministic process.